The effect of green coffee extract supplementation on blood pressure: A systematic review and meta‐analysis of randomized controlled trials. (20th August 2019) - Han, Baizhi; Nazary‐Vannani, Ali; Talaei, Sam; Clark, Cain C.T.; Rahmani, Jamal; Rasekhmagham, Reyhaneh; Kord‐Varkaneh, Hamed
Abstract : Given the proliferation in studies investigating green coffee bean extract (GCBE) supplementation, the purpose of this study was to determine the efficacy and effectiveness of GCBE supplementation on indices of blood pressure. The literature search was performed in four databases, namely, PubMed/Medline, Scopus, the Cochrane Library, and Google Scholar, to identify clinical trials that examined the effects of green coffee supplements on systolic blood pressure (SBP) and diastolic blood pressure (DBP) up to February 2019. Mean change and standard deviation (SD) of the outcome measures were used to estimate the mean difference between the intervention group and the control group at follow‐up. Nine studies reported SBP and DBP as an outcome measure. Results revealed significant reduction in SBP (weighted mean difference: −3.093 mmHg, 95% confidence interval [CI]: −3.914, −2.273; I 2 = 0.0%) and DBP (−2.170 mmHg, 95% CI: −2.749, −1.590; I 2 = 46.5%) after green coffee supplementation with low heterogeneity among the studies. In addition, in subgroup analysis, a significant reduction in SBP and DBP in studies with hypertensive patients, green coffee dosage <400 mg, and administered for 4 weeks was identified. The results of the current meta‐analysis study support the use of GCBE supplementation for the improvement of blood pressure indices, with subgroup analysis highlighting improvements in hypertensive patients.